Effects of pellet weight in ultrasonic vibration-assisted pelleting for cellulosic biofuel manufacturing. (30th October 2012) - Tang, Yongjun; Zhang, Pengfei; Liu, Defu; Pei, Z.J.
Cellulosic biofuels have been proposed to replace part of traditional liquid transportation fuels. Cellulosic biomass is the feedstock in cellulosic biofuel manufacturing. Costs associated with collection and transportation of cellulosic biomass account for more than 80% of the feedstock cost. By processing cellulosic biomass into pellets, density and handling efficiency of cellulosic feed stocks can be improved, resulting in reduction of transportation and handling costs. However, effects of pellet weight on output parameters in ultrasonic vibration-assisted pelleting (UV-A) have not been studied. This paper reports an experimental investigation of UV-A pelleting with different values of pellet weight. Output parameters studied include pellet properties (density, bulk density, and durability), pelleting temperature, charring, and sugar yield.